Impact of Perceived Social Support on Mental Health, Quality of Life, and Disability in Post–9/11 U.S. Military Veterans. Issue 1 (January 2022) - Proescher, Eric; Aase, Darrin M.; Passi, Holly M.; Greenstein, Justin E.; Schroth, Christopher; Phan, K. Luan
This study examined the impact of perceived social support on mental health and psychosocial functioning in combat veterans after military deployment, including veterans with post-traumatic stress disorder (PTSD) and veterans with comorbid PTSD and alcohol use disorder. Veterans ( n = 139; female = 23) completed self-report and clinician-administered measures of social support, mental and physical health, functional impairment, and quality of life. The cohort was divided into high, medium, and low perceived social support based on averages of the total score from the Multidimensional Scale of Perceived Social Support. Relative to the low perceived social support group, the high perceived social support group reported fewer symptoms of PTSD, anxiety, and depression. The high perceived social support group also reported a more diverse and embedded social network, less disability, and better quality of life. Of note, the high and low perceived social support groups did not differ on age, gender, education, race ethnicity, or combat trauma exposure. These findings highlight that perceived social support may play an important role in the treatment of postwar veterans as they transition back to civilian life.